If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/3(9-27x)=24-12x
We move all terms to the left:
1/3(9-27x)-(24-12x)=0
Domain of the equation: 3(9-27x)!=0We add all the numbers together, and all the variables
x∈R
1/3(-27x+9)-(-12x+24)=0
We get rid of parentheses
1/3(-27x+9)+12x-24=0
We multiply all the terms by the denominator
12x*3(-27x+9)-24*3(-27x+9)+1=0
Wy multiply elements
36x^2(--72x(-+1=0
We use the square of the difference formula
36x^2(+72x(-1=0
| 3a-5=-8 | | 32x=1/4(3/4) | | -5+x÷2=1 | | 4x+14x´+x=0 | | 2(h-8))-h=h-16 | | 8a+6=4a-14 | | y+y+10=50 | | 6(3-z)=2z+4-z | | 2x-28=6x+16 | | 5|x+1|+6=21 | | 3e=43 | | 1÷3y+1÷4=5÷12 | | 6d-4(3d+5)=0 | | 23-3t=20 | | 4(-x=4)=12 | | x^2+8x^2-9x-72=0 | | 10x+10=9x-3 | | 1/5t-3=(-17) | | 10p-30=(12+4p)-7 | | 10=7-q | | 2=x-6+1=x | | Y=2|x-3| | | y^2-7y-5=0 | | m2+6=10 | | 9+m÷3=2 | | |2x|=–4 | | 2x^2+1.8x-0.4=0 | | 0.80=(x/450) | | -9+n=-7 | | 9+n=-7 | | 6-6y=3-7y | | 0,2x=0.6(8-x) |